Letinula edodes (Berk.) Pegler (Shiitake) modulates genotoxic and mutagenic effects induced by alkylating agents in vivo - de Lima, PLA; Delmanto, R. D.; Sugui, M. M.; da Eira, A. F.; Salvadori, DMF; Speit, G.; Ribeiro, L. R. (Elsevier B.V., 2001)
We evaluated the antimutagenic effect of Letinula edodes (Berk.) Pegler (Shiitake) on the frequency of micronuclei in mice treated with N-ethyl-N-nitrosourea (ENU) or cyclophosphamide (Cl?). Mice were orally (gavage) pretreated for 15 consecutive days with solutions of Shiitake (0.6 ml per day, gavage) prepared at three different temperatures: 4, 21 (RT), and 60 degreesC. Then, the animals were intraperitoneally injected on day 15 with CP (25 or 50 mg/kg) or ENU (50 mg/kg) and killed 24 or 48 h after treatment for evaluation of micronucleated polychromatic erythrocytes (MNPCEs) in bone marrow and micronucleated reticulocytes (MNRETs). A mixture of L. edodes lineages (LE 95/016, 96/14, 96/17, 96/22, 96/23, 97/27, and 97/28) significantly decreased the frequencies of MNPCEs and MNRETs induced by CP (25 and 50 mg/kg). When a single lineage from the mixture (LE 96/17) was tested we also found a significant reduction in the frequencies of MNPCEs and MNRETs induced by both CP or ENU (50 mg/kg). The comet assay was also performed 3 h after ENU treatment using mice pretreated with the single lineage (LE 96/17) of L. edodes. The results showed a high degree of variability with some indications of an antigenotoxic effect. Taken together, our data show that solutions from Shiitake inhibit in vivo mutagenicity of CP and ENU. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Letinula edodes; antimutagenicity; N-ethyl-N-nitrosourea; cyclophosphamide; micronucleus test; comet assay